CURRENT GAIN IN UNIPOLAR PULSED DISCHARGE IN LOW-PRESSURE CARBON DIOXIDE - V. A. Lisovskiy; S. V. Dudin; N. N. Vusyk; V. A. Volkov; V. D. Yegorenkov; A. N. Dakhov; P. A. Ogloblina (East European Journal of Physics, 2017)
An unipolar low-pressure pulsed discharge (0.1-0.5 Torr) in CO2 has been investigated in the frequency range 20–200 kHz with duty cycle of 0.1 to 0.85 and voltage amplitude of 600–1000 V. It was found that the current gain phenomenon, observed earlier in the mid-frequency pulsed discharges in other gases, also occurs for a discharge in CO2 with the gain of 1–2. The gain factor decreases with the discharge current growth, both due to increase of the voltage amplitude and due to increase of carbon dioxide pressure. It is shown that the shape of the oscillogram of the pulsed discharge current is determined primarily by the duration of the plasma phase and is almost independent on the duration of the afterglow phase. A physical mechanism of the phenomenon of current gain in a pulsed discharge is discussed. It is concluded that the most important factor in this mechanism is the heating of the gas in the discharge gap during the plasma phase of the discharge, which leads to depletion of neutral gas molecule concentration and, as a consequence, to ionization rate decrease.